Parameter Estimation-Based Output Voltage or Current Regulation for Double-LCC Hybrid Topology in Wireless Power Transfer Systems - Thaís M. Tolfo; Rafael de S. Silva; Ruben B. Godoy; Moacyr A. G. de Brito; Witória S. de Souza (Energies)
In Wireless Power Transfer Systems (WPTS), variations in a load connected to a receiver can cause instability in the waveforms of output voltage and current due to their sensitivity to changes in load impedance. To overcome such drawbacks, this paper presents a control scheme for regulating voltage and current at the output of a WPTS system with the Double-LCC topology. The proposed method is based on estimating secondary-side parameters while assuming a constant coupling coefficient that remains close to its intended value during operation. The methodology begins with the mathematical modeling of the primary and secondary resonant circuits. By measuring the input voltage and current, the system estimates the load impedance, which is then used to derive the expected output voltage and a reference for the input voltage. To maintain a stable output, the system dynamically adjusts the input voltage, ensuring that it aligns with the theoretical reference value. Analytical calculations and simulations were performed using the MATLAB/Simulink platform to validate the proposed approach. Simulations confirmed the theoretical predictions for a wireless system operating at 120 kHz with a power transfer of 100 W. The results demonstrated that the load voltage remains stable at 32 V, even under varying load conditions, while the output current remains at 3 A despite fluctuations in battery voltage.